Genome-wide association of root growth angle, seminal root numbers, and leaf area in the synthetic hexaploid wheat diversity panel - Khalid, Maria; Khalid, Zoya; Ahmed, Zubair; Hickey, Lee; Rasheed, Awais; Gul, Alvina; Amir, Rabia (Elsevier B.V., 2025)
A lack of understanding about the variations in root number, root angle, and leaf area contributes to inability of wheat withstand drought stress during seedling stage. This discrepancy hinders the development of drought-tolerant wheat varieties. We aimed to evaluate germplasm at seedling stage to find association between markers and traits. We characterized a collection of synthetic hexaploid wheat for root angle, seminal root numbers, and early vigor and identified loci associated with these traits using a 50 K SNP array and genotyping-by-sequencing (GBS) platforms. In total, 39 marker-trait nucleotides (QTNs) were associated with LA, RA, and RN distributed over 10 wheat chromosomes. Out of these, 11 QTNs were associated with LA, 15 QTNs were associated with RA, and 13 QTNs were associated with RN.LA showed a negative correlation with RN and a poor correlation with RA. The phenotypic values of synthetic hexaploid wheat accessions with a higher frequency of favorable alleles have been found to increase. Therefore, prioritizing the use of these synthetic wheat varieties in wheat breeding programs can be beneficial for improving root system architecture (RSA) and early vigor. These preliminary findings can be useful for pre-breeding efforts aimed at enhancing wheat adaptability to drought stress conditions.